Capitalisms and Democracies Can Growth and Equality be Reconciled? - Trigilia, Carlo (Routledge Advances in Sociology, 2023)
This book examines steadily-growing increases in inequality within Western capitalist democracies, examining with care the differences between these democracies rooted in their culture and institutions. It highlights the differences in growth and inequalities between different countries, pointing to the role of endogenous institutions that affect social inequalities as well as the relationship between redistribution and economic growth. The book presents extensive comparative research on institutional factors such as industrial relations, welfare systems, training and innovation policies. Paying attention to diverse types of democracies and to the main features of left-wing parties, the book highlights the importance of politics, and of different types of democracies, in shaping social inequalities and diverse development paths. It will appeal to students and scholars interested in economic and labour sociology, welfare studies, comparative political economy, comparative welfare, varieties of capitalism, and comparative politics.